Adhesives, adhesive sheets and flexible copper-clad laminates

JP7644439B2Active Publication Date: 2025-03-12HEFEI HANZHIHE MATERIAL SCI & TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020152144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-10
Publication Date
2025-03-12
Estimated Expiration
2040-09-10

AI Technical Summary

Benefits of technology

【0017】 本発明の接着剤は、200℃で90分間加熱処理してフィルムを作成した場合に、誘電正接が0.003(5GHz)以下、誘電率が3.0(5GHz)以下、及びTgが110℃以上となり、保存安定性が非常に良好で、吸水率の低いフィルムを作成することができる。Tgが110℃以上であるため、常用使用温度110℃以下では誘電特性の急激な変化を起こさない材料を提供することができる。また、本発明の接着剤を用いてポリイミドフィルム基材と銅箔を接着させることにより、誘電率及び誘電正接が低く、耐熱性及び引きはがし強さが良好なフレキシブル銅張積層板を作成でき、誘電特性と、熱的特性(Tg)、加工特性、接着特性、吸湿特性及びコストとをバランス良く並立できるフレキシブル銅張積層板を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644439000001
    Figure 0007644439000001
  • Figure 0007644439000002
    Figure 0007644439000002
  • Figure 0007644439000003
    Figure 0007644439000003
Patent Text Reader

Abstract

To provide an adhesive for a flexible copper-clad laminate, capable of achieving dielectric characteristics, thermal characteristics, working characteristics, adhesion characteristics, and moisture absorption characteristics, and costs in good balance without using a cross-linking agent, and to provide an adhesive sheet and a flexible copper-clad laminate manufactured by using the same.SOLUTION: An adhesive for a flexible copper-clad laminate, to be used for adhering a polyimide film base material to a copper foil contains: a solvent-soluble polyimide having a repeating unit represented by the following general formula [I] and subjected to dehydrating and ring-closing imidization; and a silane coupling agent represented by the following general formula [II]. (In formula [I], Z is a bisphenol type acid dianhydride residue, and Ar is a dimer diamine residue and / or a fluorine-containing diamine residue.) (RO)3Si-X [II] (in formula [II], X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flexible copper clad laminate (FCCL) used in flexible printed wiring boards and the like, and an adhesive and an adhesive sheet for producing the same. [Background technology]

[0002] In recent years, with the trend toward lighter, smaller, and denser electronic products, the demand for various printed wiring boards, especially flexible printed wiring boards, has been growing. Flexible printed wiring boards have a circuit made of metal foil formed on an insulating film. Flexible copper-clad laminates for flexible printed wiring boards generally have a structure in which an insulating film such as a polyimide film is used as a substrate, and a metal foil is laminated on the surface of the substrate by heating and pressing through various adhesive layers.

[0003] On the other hand, the fifth generation mobile communication system (5G) has dramatically improved three functions: high speed and large capacity, low signal latency, and simultaneous multiple connection of terminals. Therefore, for flexible copper-clad laminates, adhesive materials suitable for electronic components for 5G communication and millimeter-wave radar used in autonomous driving are also required. 5G communication and millimeter-wave radar require communication in a new frequency band of 20 GHz or more, called the millimeter-wave region, in addition to the conventionally used frequency band of 6 GHz or less. For this reason, for flexible copper-clad laminates, adhesive materials that satisfy the dielectric properties suitable for communication in high frequency bands, heat resistance that can withstand semiconductor mounting, physical properties such as adhesion to conductor wiring, and good processing characteristics are also required.

[0004] In high-frequency circuits, dielectric loss is a major problem, especially in insulating materials. These losses manifest themselves as problems such as heat generation, noise, and high power consumption during signal transmission. Dielectric loss is proportional to the root of the frequency, the dielectric tangent of the material, and the dielectric constant, but for insulating materials, reducing the dielectric tangent is a major challenge. This type of dielectric loss problem becomes noticeable above 1 GHz in frequency bands. The dielectric tangent reflects the phenomenon in which a delay occurs in the vibration caused by an external electric field, mainly at oriented polarization sites in the material structure, causing the dipoles in the insulating material to be unable to follow the vibration of the electric field, resulting in the consumption of kinetic energy.

[0005] Therefore, molecular design from the viewpoint of suppressing the motion induced by an external electric field by making the molecular structure of the resin non-polarized is effective in reducing dielectric loss. In other words, in order to reduce dielectric loss in the high frequency band, it is necessary to suppress the motion of polarization in the polymer structure (dielectric loss tangent) and to reduce polarization (dielectric constant).

[0006] Conventionally, various adhesives containing polyimide have been reported as adhesive materials for copper-clad laminates used in flexible printed wiring boards (Patent Documents 1 to 7). Among them, adhesives containing polyimide having bisphenol-type dianhydride residues and dimer diamine residues, a crosslinking agent, and a reactive alkoxysilyl compound have been reported as adhesives aiming at low dielectric properties (Patent Documents 2 to 7). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-199645 A [Patent Document 2] JP 2017-121807 A [Patent Document 3] JP 2018-168369 A [Patent Document 4] JP 2018-168370 A [Patent Document 5] JP 2018-168371 A [Patent Document 6] JP 2019-172989 A [Patent Document 7] JP 2020-105493 A Summary of the Invention [Problem to be solved by the invention]

[0008] As mentioned above, various adhesives have been reported as adhesives for copper-clad laminates containing polyimide resins, but the conventional adhesives contain crosslinking agents such as epoxy as essential components, which causes problems such as a larger dielectric tangent and lower heat resistance compared to polyimide resins that do not contain such crosslinking agents. In addition, the reactive alkoxysilyl compounds specifically used in conventional adhesives are amino-based compounds, and although the use of amino-based compounds is effective in improving adhesive strength, there is a problem that the storage stability, which is a basic characteristic of an adhesive, is reduced. Furthermore, there is also a problem that the heat resistance, especially Tg, is reduced when the amount of dimer diamine in the total diamine increases.

[0009] The present inventors have found that, in order to simultaneously achieve the adhesive strength between the substrate and the copper foil, the solder heat resistance, and the storage stability, which are essential characteristics of an adhesive, it is effective to use a reactive alkoxysilyl compound having a ketimine structure or an aldimine structure as an additive, which is expected to improve the adhesive strength equal to or greater than that of an amino-based alkoxysilyl compound and improve the solder heat resistance after moisture absorption, and which can suppress the decrease in storage stability, which is a drawback of amino-based compounds. In addition, the present inventors have found that it is preferable to limit the amount of dimer diamine, which is essential for the low dielectric properties required for FCCL, in order to achieve a balance between the basic properties of Tg, adhesive properties, and moisture absorption properties, and processing properties such as processability and mountability. And, based on the above findings, it is possible to achieve high Tg, excellent moisture absorption properties, and low dielectric properties while simultaneously achieving both adhesive strength and storage stability, even without adding a crosslinking agent, which was previously essential, and thus the present invention has been completed.

[0010] The present invention has been made in consideration of the above circumstances, and its object is to provide an adhesive for flexible copper-clad laminates that can achieve a good balance of dielectric properties, thermal properties, processing properties, adhesive properties, moisture absorption properties, and cost without the need for a crosslinking agent, and an adhesive sheet and flexible copper-clad laminate produced using the same. Another object of the present invention is to provide an adhesive for flexible copper-clad laminates that uses a ring-closed polyimide as an adhesive and can achieve non-dehydration shrinkage and low-temperature operation that cannot be achieved with polyamic acid-type polyimides, and an adhesive sheet and flexible copper-clad laminates manufactured using the adhesive. Such non-dehydration shrinkage and low-temperature operation can reduce warping and improve dimensional stability in large panel sizes. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have focused on the fact that dielectric properties (dielectric constant, dielectric loss tangent) depend on frequency, are significantly affected by the temperature and humidity of the usage environment, and the value of the dielectric properties changes significantly at the boundary of the Tg of the resin itself contained in the adhesive. They have then discovered that an adhesive for flexible copper-clad laminates that can simultaneously achieve a good balance between dielectric properties, thermal properties (Tg), processing properties, adhesive properties, moisture absorption properties, and cost can be realized by using a silane coupling agent having a specific structure together with a solvent-soluble polyimide that has been subjected to dehydration ring-closing imidization, and have completed the present invention.

[0012] That is, the present invention provides an adhesive for flexible copper-clad laminates for bonding a polyimide film substrate and a copper foil that constitute a flexible copper-clad laminate, the adhesive comprising a solvent-soluble polyimide that has been subjected to dehydration ring-closure imidization and has a repeating unit represented by the following general formula [I] and a silane coupling agent represented by the following general formula [II]: (However, silane coupling agents having amino groups are excluded.) Contains and the diamine residue contained in the solvent-soluble polyimide is 20 mol % or more and less than 30 mol % of all diamine residues. Adhesive, to be provided. [ka] (In the formula, Z is a bisphenol dianhydride residue, and Ar is Dimer diamine residue is) (RO)3Si-X [II] (In the formula, X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)

[0013] [ka] (In the formula, Z is a bisphenol dianhydride residue, and Ar is a dimer diamine residue and / or a fluorine-containing diamine residue.) (RO)3Si-X [II] (In the formula, X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)

[0014] The present invention also provides an adhesive sheet for flexible copper-clad laminates, comprising an adhesive layer for adhering copper foil laminated on one or both sides of a polyimide film substrate constituting the flexible copper-clad laminate, the adhesive layer containing the adhesive of the present invention.

[0015] The present invention also provides a flexible copper-clad laminate comprising an adhesive layer and a copper foil laminated in that order on one or both sides of a polyimide film substrate, the adhesive layer containing the adhesive of the present invention.

[0016] The present invention further provides a method for producing the flexible copper-clad laminate of the present invention, the method comprising laminating a copper foil to the adhesive sheet of the present invention at a temperature of 220°C or less, and then heat-treating the adhesive layer at a temperature of 220°C or less. Effect of the Invention

[0017] When the adhesive of the present invention is heated at 200°C for 90 minutes to produce a film, it has a dielectric loss tangent of 0.003 (5GHz) or less, a dielectric constant of 3.0 (5GHz) or less, and a Tg of 110°C or more, and can produce a film with very good storage stability and low water absorption. Since the Tg is 110°C or more, it is possible to provide a material that does not undergo a sudden change in dielectric properties at a normal use temperature of 110°C or less. In addition, by bonding a polyimide film substrate and a copper foil using the adhesive of the present invention, it is possible to produce a flexible copper-clad laminate with a low dielectric constant and dielectric loss tangent, good heat resistance and peel strength, and a flexible copper-clad laminate that can balance dielectric properties with thermal properties (Tg), processing properties, adhesive properties, moisture absorption properties, and cost.

[0018] In addition, the adhesive layer of the adhesive sheet and the copper foil can be bonded together at a temperature of 220° C. or less, and the adhesive layer can be heat-treated at a temperature of 220° C. or less. This eliminates the need for a lamination process at high temperature and pressure, which is one of the main causes of deterioration of dimensional stability, and improves the dimensional stability of the flexible copper-clad laminate.

[0019] Flexible copper clad laminates (FCCLs) produced using the adhesive of the present invention are used for flexible printed wiring boards, etc., and have particularly superior dielectric properties (dielectric constant, dielectric tangent) than conventional two-layer FCCLs, while other properties and processability are equal to or better than those of two-layer FCCLs. Therefore, hereinafter, the flexible copper clad laminate of the present invention is also referred to as a low dielectric two-layer FCCL. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The adhesive for flexible copper-clad laminates of the present invention is an adhesive for bonding the polyimide film substrate and copper foil that constitute a flexible copper-clad laminate, and contains a dehydrated, ring-closed imidized, solvent-soluble polyimide having a repeating unit represented by the following general formula [I], and a silane coupling agent represented by the general formula [II].

[0021] [ka]

[0022] (In the formula, Z is a bisphenol dianhydride residue, and Ar is a dimer diamine residue and / or a fluorine-containing diamine residue.) (RO)3Si-X [II] (In the formula, X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)

[0023] (Solvent-soluble polyimide) The solvent-soluble polyimide of the present invention may contain other repeating units as long as it contains the repeating unit represented by the above general formula [I] as a part thereof. In the repeating unit represented by the general formula [I], Z is a bisphenol-type dianhydride residue. The bisphenol-type dianhydride for introducing the bisphenol-type dianhydride residue into the polyimide is not particularly limited as long as it has a bisphenol-type structure, and examples thereof include 4,4'-(4,4'-isopropylidenediphenoxy)bis(phthalic anhydride) (hereinafter also referred to as BPADA) and 4,4'-(4,4'-methylenediphenoxy)bis(phthalic anhydride). Among these, BPADA is preferred. Commercially available BPADA products include BISDA-1000 and BISDA-3000 manufactured by SABIC Innovative Plastics Japan LLC.

[0024] The other repeating units have a dicarboxylic acid anhydride residue other than the bisphenol-type dianhydride residue (Z). The dicarboxylic acid anhydride residue other than the bisphenol-type dianhydride residue (Z) may be a fluorine-containing dianhydride residue. Examples of the fluorine-containing dianhydride for introducing the fluorine-containing dianhydride residue into the polyimide include fluorine-containing aromatic tetracarboxylic acid dianhydrides such as 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride, and 3,3'-(hexafluoroisopropylidene)diphthalic anhydride.

[0025] The above-mentioned fluorine-containing acid dianhydride may be a tetracarboxylic acid dianhydride having no fluorine atom, in which some or all of the hydrogen atoms are replaced with a substituent having a fluorine atom.Specific examples of the substituent having a fluorine atom include fluoro, fluoromethyl, difluoromethyl, trifluoromethyl, trifluoromethoxy, HCF2CF2-, CF3CF2-, CF3CH2-, CF3CF2CF2CF2-, and CF3CF2CF2CH2-, and more preferably fluoro, fluoromethyl, difluoromethyl, trifluoromethyl, CF3CF2-, and HCF2CF2-. Examples of tetracarboxylic dianhydrides not having fluorine atoms include cyclohexane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, dicyclohexane-3,4,3',4'-tetracarboxylic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 4,4'-(methylidene)diphthalic anhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, and bis(3,4-dicarboxyphenyl)sulfonate. 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 1,3-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 1,4-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 2,2-bis{4-[4-(1,2-dicarboxy)furan dianhydride} 2,2-Bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, 4,4'-bis[4-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, 4,4'-Bis[3-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride Examples of suitable dianhydrides include bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, and 1,2,7,8-phenanthrenetetracarboxylic dianhydride.

[0026] The content of the bisphenol dianhydride component (Z component) constituting the solvent-soluble polyimide is preferably 70 mol % or more, more preferably 75 mol % or more, and particularly preferably 80 mol % or more of the total dicarboxylic acid anhydride components, from the viewpoint of achieving low dielectric properties and high Tg.

[0027] On the other hand, in polyimides having fluorine-containing dianhydride residues, physical properties such as dielectric constant and water absorption are determined almost entirely by the content of fluorine atoms and imide groups in the polyimide, and are not related to the chemical structure (primary structure) or electronic structure. Therefore, in order to control these physical properties, it is sufficient to appropriately select a fluorine-containing dianhydride within a range that does not impair the reactivity and heat resistance of the resulting polyimide.

[0028] In the repeating unit represented by the above general formula [I], Ar is a dimer diamine residue and / or a fluorine-containing diamine residue. The dimer diamine for introducing a dimer diamine residue into a polyimide is a dimer of an unsaturated fatty acid such as oleic acid, in which all carboxyl groups of the dimer acid are replaced with primary amino groups, and further includes hydrogenated dimer diamine obtained by hydrogenation (see JP-A-9-12712, etc.), and various known dimer diamines can be used without particular limitation. Below, non-limiting general formulas of dimer diamines are shown (in each formula, m+n=6 to 17 is preferable, p+q=8 to 19 is preferable, and the dashed line portion represents a carbon-carbon single bond or a carbon-carbon double bond). Dimer diamines having an alicyclic structure are more preferable.

[0029] [ka]

[0030] Since dimer diamine has a macromolecular aliphatic or alicyclic structure with a molecular weight of about 530 to 620, it can increase the molecular molar volume and relatively reduce the polar groups of polyimide. In addition, since it has two freely movable hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, it not only gives flexibility to polyimide but also makes polyimide have an asymmetric chemical structure or a non-planar chemical structure, and as a result, it is possible to reduce the dielectric constant and dielectric loss tangent of polyimide. Dimer diamine residues can reduce interactions such as π-π stacking between polymer chains, improve solubility in solvents, and can make charge transfer (CT) between aromatic diamine residues and aromatic ditetracarboxylic anhydride residues less likely to occur.

[0031] Commercially available dimer diamine products include VERSAMINE 551 (manufactured by Cognics Japan K.K.), VERSAMINE 552 (manufactured by Cognics Japan K.K.; a hydrogenated product of VERSAMINE 551), PRIAMINE 1075, and PRIAMINE 1074 (all manufactured by Croda Japan K.K.).

[0032] Examples of fluorine-containing aromatic diamines for introducing fluorine-containing diamine residues into polyimides include fluorine-containing aromatic diamines such as 2,2'-bis(trifluoromethyl)benzidine, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2'-bis(4-aminophenyl)hexafluoropropane, and 1,3-diamino-2,4,5,6-tetrafluorobenzene.

[0033] From the viewpoint of obtaining low dielectric properties and high Tg, the content of the dimer diamine component (Ar component) constituting the solvent-soluble polyimide is preferably set to have a lower limit of 20 mol % or more, 21 mol % or more, 22 mol % or more, 23 mol % or more, 24 mol % or more, 25 mol % or more, 26 mol % or more, or 27 mol % or more of the total diamine components, and an upper limit of less than 30 mol %, and more preferably 29 mol % or less of the total diamine components.

[0034] When a dimer diamine is used as the Ar component, it is preferable to further improve Tg, and when a fluorine-containing aromatic diamine is used, it is preferable to further improve Tg and adhesive performance. Therefore, even when a dimer diamine and / or a fluorine-containing aromatic diamine is used as the Ar component, it is preferable to use other diamine components in combination in order to balance properties including Tg and adhesive performance.

[0035] On the other hand, in polyimides having fluorine-containing diamine residues, physical properties such as dielectric constant and water absorption are determined almost entirely by the content of fluorine atoms and imide groups in the polyimide, and are not related to the chemical structure (primary structure) or electronic structure. Therefore, in order to control these physical properties, it is sufficient to appropriately select a fluorine-containing diamine within a range that does not impair the reactivity and heat resistance of the resulting polyimide.

[0036] The solvent-soluble polyimide may be a block-lock copolymer having a repeating unit other than the repeating unit represented by the above general formula [I], and is also effective in compensating for the above-mentioned shortcomings of dimer diamines and fluorine-containing aromatic diamines.

[0037] Examples of the other aromatic diamines include p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, 2,4-diaminoxylene, 2,4-diaminodurene, 4,4'-diaminodiphenylmethane, 4,4'-methylenebis(2-methylaniline), 4,4'-methylenebis(2-ethylaniline), 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-methylenebis(2,6-diethylaniline), 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl m ... Aminobenzophenone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzanilide, 4-aminophenyl-4'-aminobenzoate, benzidine, 3,3'-dihydroxybenzidine, 3,3'-dimethoxybenzidine, o-tolidine, m-tolidine, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(3-aminophenoxy)phenyl)sulfone, bis(4-(4-aminophenoxy)phenyl)sulfone, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 9,9-bis(4-aminophenyl)fluorene, and the like.

[0038] The solvent-soluble polyimide having the repeating unit represented by the above general formula [I] can be obtained by subjecting a bisphenol-type acid dianhydride to a dehydration condensation reaction with a dimer diamine and / or a fluorine-containing diamine.

[0039] The method for synthesizing the solvent-soluble polyimide may be a known method and is not particularly limited, but the above-mentioned bisphenol-type acid dianhydride and dimer diamine and / or fluorine-containing diamine are reacted in approximately equal amounts in an organic polar solvent in the presence of a catalyst and a dehydrating agent at 160 to 200° C. for several hours to synthesize the solvent-soluble polyimide. As the organic polar solvent, N-methylpyrrolidone (NMP), γ-butyrolactone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, tetramethylurea, tetrahydrothiophene-1,1-oxide, etc. are used.

[0040] The solvent-soluble polyimide is preferably a block copolymer, and the block copolymer can be synthesized by performing a block copolymerization reaction. For example, it can be produced by a two-stage sequential addition reaction, in which a polyimide oligomer is synthesized from a bisphenol-type acid dianhydride and a dimer diamine and / or a fluorine-containing diamine in the first stage, and then a fluorine-containing diamine and / or a dimer diamine is further added in the second stage to perform polycondensation to obtain a block copolymer polyimide.

[0041] As a catalyst for block copolymerization, a two-component acid-base catalyst utilizing the equilibrium reaction of lactones can be used to promote the dehydration imidization reaction. Specifically, a two-component catalyst of γ-valerolactone and pyridine or N-methylmorpholine is used. As shown in the formula below, as the imidization proceeds, water is generated, and the generated water participates in the equilibrium of lactones, becoming an acid-base catalyst and exhibiting catalytic action.

[0042] [ka]

[0043] The water produced by the imidization reaction is removed from the system by azeotropy with a dehydrating agent such as toluene or xylene that coexists in the polar solvent. When the reaction is completed, the water in the solution is removed, and the acid-base catalyst becomes γ-valerolactone and pyridine or N-methylmorpholine, which are removed from the system. In this way, a high-purity polyimide solution can be obtained.

[0044] Other two-component catalysts include oxalic acid or malonic acid and pyridine or N-methylmorpholine. In a reaction solution at 160 to 200°C, oxalates or malonates act as acid catalysts to promote the imidization reaction. A catalytic amount of oxalic acid or malonic acid remains in the generated polyimide solvent. When this polyimide solution is applied to a substrate and then heated to 200°C or higher to remove the solvent and form a film, the oxalic acid or malonic acid remaining in the polyimide is thermally decomposed as shown in the following formula and removed from the system as a gas.

[0045] [ka]

[0046] By the above method, a high-purity, solvent-soluble polyimide can be obtained. The oxalic acid-pyridine catalyst has stronger activity than the valerolactone-pyridine catalyst, and can produce a high-molecular-weight polyimide in a short time.

[0047] The molecular weight of the synthesized solvent-soluble polyimide is preferably 10,000 to 400,000 in terms of polystyrene equivalent weight average molecular weight (Mw). When the molecular weight of the solvent-soluble polyimide is within this range, it is preferable because good solvent solubility, film properties, and insulating properties can be achieved. The term "solvent-soluble" in the present invention is used for the organic polar solvent used in the synthesis of polyimide and the solvent used in the adhesive composition described later, and means that a solution of polyimide with a solid content of 20% by weight can be prepared using these solvents. Examples of the solvent include NMP, γ-butyrolactone, DMF, DMAC, etc. The synthesized polyimide can be used in the form of a solution dissolved in the organic polar solvent or the solvent used in the adhesive composition described later so that the solid content is, for example, 10 to 30% by weight.

[0048] In addition, since the solvent-soluble polyimide of the present invention is a polyimide that has been completely imidized by dehydration and ring closure, it does not require high-temperature heat treatment for imidization after the adhesive is applied to the polyimide film substrate. Therefore, compared with polyamic acid (polyimide precursor), which requires high-temperature heat treatment (300°C or higher) for imidization after the adhesive is applied to the polyimide film substrate, there is an advantage in that a flexible copper-clad laminate with high dimensional stability can be provided.

[0049] (Silane coupling agent) The silane coupling agent of the present invention has a structure represented by the following general formula [II]. (RO)3Si-X [II] (In the formula, X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)

[0050] The group having a ketimine structure represented by X is a group represented by general formula (1): -R1-N=CR2R3, and the group having an aldimine structure represented by X is a group represented by general formula (2): -R1-N=CHR2.

[0051] In the general formulas (1) and (2), R1 is an alkylene group having 1 to 10 carbon atoms, preferably 2 to 7 carbon atoms, and R 2、 R3 is a linear or branched alkyl group having 1 to 10 carbon atoms, preferably 1 to 7 carbon atoms, or a phenyl group which may be substituted. R is an alkyl group, preferably a linear or branched alkyl group having 1 to 7 carbon atoms, more preferably 1 to 5 carbon atoms, and particularly preferably 1 to 3 carbon atoms.

[0052] Examples of the silane coupling agent of the present invention include those having a ketimine structure, such as 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine (Compound III below), 3-trimethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-(1-phenylethylidene)-3-(triethoxysilyl)-1-propylamine, and N-(1-phenylethylidene)-3-(trimethoxysilyl)-1-propylamine.

[0053] [ka]

[0054] Furthermore, examples of compounds having an aldimine structure include N-(phenylmethylene)-3-(triethoxysilyl)-1-propylamine (Compound IV) and N-(phenylmethylene)-3-(trimethoxysilyl)-1-propylamine.

[0055] [ka]

[0056] Commercially available products equivalent to the silane coupling agent of the present invention include KBE-9103P (ketimine structure) and X-12-1172ES (aldimine structure) manufactured by Shin-Etsu Chemical Co., Ltd.

[0057] General silane coupling agents have organic functional groups such as vinyl, epoxy, styryl, methacryl, acrylic, amino, ureido, mercapto, and isocyanate groups. For the solvent-soluble polyimide of the present invention, silane coupling agents having amino groups are suitable, but the amino groups have high reactivity, which reduces the storage stability of the adhesive. By using a silane coupling agent having a ketimine structure or aldimine structure with a protected amino group, it is expected that the adhesive strength will be improved to the same level as or higher than that of an amino group-containing alkoxysilyl compound, and the deterioration of the storage stability of the adhesive can be suppressed.

[0058] In the present invention, in order to reduce the dielectric constant, the dielectric loss tangent and the water absorption rate, the introduction of polar groups into the solvent-soluble polyimide is suppressed as much as possible, and the amount of dimer diamine is also limited. Since these polar groups and dimer diamine are related to the adhesive strength, the adhesive strength of the adhesive tends to decrease, but by using the silane coupling agent of the present invention, the appropriate adhesive strength can be ensured, and at the same time, the solder heat resistance after moisture absorption can be improved.

[0059] The amount of the silane coupling agent of the present invention added to the adhesive is preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, particularly preferably 0.5 parts by weight or more, and the upper limit is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, particularly preferably 5 parts by weight or less, based on 100 parts by weight of the solid content of the polyimide solution. If the lower limit of the amount of the silane coupling agent added is less than 0.01 parts by weight, the peel strength of the adhesive tends to decrease. Also, if the upper limit of the amount of the silane coupling agent added exceeds 10 parts by weight, the storage stability and peel strength of the adhesive tend to decrease.

[0060] (non-aqueous solvent) The adhesive of the present invention may be diluted with a non-water-soluble solvent to reduce the moisture absorption performance of the adhesive, such as storage stability. NMP and γ-butyrolactone are optimal organic polar solvents used in the organic synthesis of polyimide, but since these are water-soluble solvents, it is preferable to dilute them with a non-water-soluble solvent. As a non-water-soluble solvent, methyl benzoate or the like is optimal.

[0061] (glue) The adhesive for flexible copper-clad laminates of the present invention may be an adhesive composition that contains, in addition to the above-mentioned solvent-soluble polyimide, silane coupling agent, and water-insoluble solvent, a flame retardant, an imidizing agent, a filler, and the like. The filler is preferably one having low dielectric properties. From the viewpoint of settling properties as an adhesive and processability as an FCCL, a submicron or nano-filler of silica is particularly preferred.

[0062] The adhesive (composition) can be produced by mixing the solvent-soluble polyimide with other resin components and other ingredients as necessary, adding a solvent to the resulting mixture, and preparing a resin varnish with a resin solid content of 20 to 60% by weight.

[0063] (Physical properties of adhesive film) The adhesive (composition) of the present invention is a film obtained by heating an adhesive film in a low volatile state made from the adhesive (composition) at 200°C for 90 minutes, and the dielectric tangent of the film is 0.003 (5GHz) or less, the dielectric constant is 3.0 (5GHz) or less, and the Tg (glass transition temperature) is 110°C or more. The dielectric properties of a resin change rapidly at the Tg. From this viewpoint, it is desired that the Tg (glass transition temperature) of the film made from the adhesive is higher than the normal use temperature of electronic devices and the like in which FCCL made using this adhesive is used. Therefore, in the present invention, the lower limit of the Tg (glass transition temperature) of the film made from the adhesive is preferably 110°C or more, more preferably 120°C or more, and particularly preferably 130°C or more, and the upper limit is preferably 190°C or less, more preferably 180°C or less, and particularly preferably 170°C or less.

[0064] (Adhesive sheet) The adhesive (composition) of the present invention is applied to one or both sides of a polyimide film substrate, and heated to reduce volatility, thereby obtaining an adhesive sheet for a low dielectric two-layer FCCL by the lamination method. Specifically, as described above, a resin varnish prepared by diluting the adhesive (composition) of the present invention with a suitable organic solvent such as NMP or γ-butyrolactone is applied to one or both sides of a polyimide film substrate, which is the core material, using a die coater, gravure coater, or the like.

[0065] The coating thickness of the adhesive layer must be at least the minimum thickness that can embed the roughened surface of the copper foil to be laminated, and specifically, the thickness is preferably at least the Rz of the copper foil (measured according to JIS B 0601-2001). However, this coating thickness affects the dielectric properties of the FCCL, so it is changed according to the target dielectric properties.

[0066] The coating temperature of the adhesive layer (including the drying temperature after coating) is preferably the minimum temperature at which the contained solvent can be reduced in volatility. From this viewpoint, the coating temperature of the adhesive layer is preferably 150° C. or higher, more preferably 160° C. to 180° C. The drying temperature after coating of the adhesive layer is preferably 220° C. or lower, more preferably 190° C. to 210° C., particularly preferably 180° C. to 200° C.

[0067] (Laminated low dielectric two-layer flexible copper-clad laminate) After bonding (laminating) copper foil to the surface of the adhesive layer of the adhesive sheet prepared as described above, the adhesive layer is heat-treated to prepare a laminated low dielectric two-layer flexible copper-clad laminate. The upper limit of the lamination temperature is preferably 220°C or less, more preferably 210°C or less, and particularly preferably 200°C or less, and the lower limit is preferably 170°C or more, more preferably 175°C or more, and particularly preferably 180°C or more. Since the heat treatment temperature of the adhesive layer is the largest factor of thermal distortion, the upper limit is preferably 220°C or less, more preferably 210°C or less, and particularly preferably 200°C or less, and the lower limit is preferably 180°C or more, more preferably 185°C or more, and particularly preferably 190°C or more. EXAMPLES

[0068] The present invention will be described in detail below based on examples. However, the present invention can be modified into various other embodiments and is not limited to the following examples.

[0069] 1. Synthesis of solvent-soluble polyimide resin (Synthesis Example 1) A three-necked separable glass flask was fitted with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 67.6 g (0.13 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 35.69 g (0.065 mol) of PRIAMINE 1075 (manufactured by Croda Japan Co., Ltd.), 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 360 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 3 hours. During the reaction, the toluene-water azeotrope was removed. After cooling to room temperature, 49.92g (0.096mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 50.53g (0.145mol) of 9,9-bis(4-aminophenyl)fluorene, 3.22g (0.016mol) of 4,4'-diaminodiphenyl ether, 130g of NMP, and 30g of toluene were added and stirred at room temperature for 30 minutes, then the temperature was raised to 180°C and heated and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 3 hours and 30 minutes while removing the water-toluene azeotropic reflux from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0070] (Synthesis Example 2) A three-necked separable glass flask was fitted with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 55.12 g (0.106 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 29.65 g (0.054 mol) of PRIAMINE 1075 (manufactured by Croda Japan Co., Ltd.), 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 390 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 3 hours. During the reaction, the toluene-water azeotrope was removed. After cooling to room temperature, 83.72g (0.161mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 34.04g (0.170mol) of 4,4'-diaminodiphenyl ether, 14.98g (0.043mol) of 9,9-bis(4-aminophenyl)fluorene, 110g of NMP, and 30g of toluene were added and stirred at room temperature for 30 minutes, then the temperature was raised to 180°C and heated and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 2 hours and 30 minutes while removing the water-toluene azeotropic reflux from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0071] (Synthesis Example 3) A three-necked glass separable flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 80.08 g (0.154 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 42.27 g (0.077 mol) of PRIA MINE1075 (manufactured by Croda Japan Co., Ltd.), 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 390 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 3 hours. During the reaction, the toluene-water azeotrope was removed. After cooling to room temperature, 58.76g (0.113mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 60.85g (0.190mol) of 2,2'-bis(trifluoromethyl)benzidine, 160g of NMP, and 30g of toluene were added, and the mixture was stirred at room temperature for 30 minutes, then heated to 180°C and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 3 hours and 30 minutes while removing the water-toluene azeotropic reflux from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0072] (Synthesis Example 4) A three-necked separable glass flask was fitted with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 80.08 g (0.154 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 42.27 g (0.077 mol) of PRIAMINE 1075 (manufactured by Croda Japan Co., Ltd.), 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 430 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 3 hours. During the reaction, the toluene-water azeotrope was removed. After cooling to room temperature, 58.76g (0.113 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 30.44g (0.152 mol) of 4,4'-diaminodiphenyl ether, 13.24g (0.038 mol) of 9,9-bis(4-aminophenyl)fluorene, 85g of NMP, and 30g of toluene were added and stirred at room temperature for 30 minutes, then the temperature was raised to 180°C and heated and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 2 hours and 30 minutes while removing the water-toluene azeotropic reflux from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0073] (Synthesis Example 5) 12 g of Admanano 10 nm (manufactured by Admatechs Co., Ltd.) and 48 g of NMP were added to 100 g of the block copolymer polyimide solution having a solid content of 20% by weight produced in Example 1, and the mixture was kneaded for 2 hours using a centrifugal mixer “Awatori Rentaro” (manufactured by Thinky Corporation) to obtain a block copolymer polyimide solution having a solid content of 20% by weight.

[0074] (Comparative Synthesis Example 1) A three-necked separable glass flask was fitted with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 138.97 g (0.267 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 53.46 g (0.267 mol) of 3,4'-diaminodiphenyl ether, 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 450 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 3 hours and 30 minutes while removing the reflux product of the water-toluene azeotrope from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0075] (Comparative Synthesis Example 2) A glass separable three-neck flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 138.97 g (0.267 mol) of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 117.49 g (0.214 mol) of PRIAMINE 1075 (manufactured by Croda Japan Co., Ltd.), 10.61 g (0.053 mol) of 4,4'-diaminodiphenyl ether, 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 670 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 4 hours and 30 minutes while removing the water-toluene azeotropic reflux product from the system. The resulting product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0076] (Comparative Synthesis Example 3) A three-necked separable glass flask was fitted with a stirrer, a nitrogen inlet tube, and a cooling tube equipped with a water receiver. 68.41 g (0.154 mol) of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 42.27 g (0.077 mol) of PRIAMINE 1075 (manufactured by Croda Japan Co., Ltd.), 1.5 g (0.015 mol) of valerolactone, 2.4 g (0.03 mol) of pyridine, 340 g of NMP, and 90 g of toluene were charged and stirred at room temperature under a nitrogen atmosphere at 200 rpm for 30 minutes, and then heated to 180°C and stirred for 3 hours. During the reaction, the toluene-water azeotrope was removed. After cooling to room temperature, 50.20g (0.113 mol) of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 60.85g (0.190 mol) of 2,2'-bis(trifluoromethyl)benzidine, 160g of NMP, and 30g of toluene were added and stirred at room temperature for 30 minutes, then the temperature was raised to 180°C and heated and stirred for 1 hour. The reaction was terminated by heating and stirring at 180°C for 2 hours and 30 minutes while removing the water-toluene azeotropic reflux from the system. The obtained product was diluted with methyl benzoate to obtain a block copolymer polyimide solution with a solid content of 20% by weight.

[0077] 2. Preparation of the adhesive composition Adhesive compositions 1 to 5 were prepared by adding 1 part of a silane coupling agent KBE-9103P (manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of solid content to 100 parts by weight of the polyimide solutions synthesized in Synthesis Examples 1 to 5 and stirring the mixture. An adhesive composition 6 was prepared by adding 1 part of a silane coupling agent KBE-903 (manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of solid content to 100 parts of the polyimide solution synthesized in Synthesis Example 1 and stirring the mixture. The polyimide solutions synthesized in Comparative Synthesis Examples 1 and 2 were directly used as adhesive compositions without adding a silane coupling agent.

[0078] (Dielectric constant, dissipation factor and Tg of adhesive film) The dielectric properties and Tg of films prepared from the adhesive compositions 1 to 6 and the polyimide solutions (resin varnishes) synthesized in Comparative Synthesis Examples 1 and 2 were measured by the following method. The adhesive composition or resin varnish was applied to the shiny side of 18 μm electrolytic copper foil with a bar coater and dried at a temperature of 160 ° C to produce adhesive-attached copper foil (adhesive thickness: about 21 μm). The volatile content of the solvent was adjusted to 0.6 wt %. The shiny side of 18 μm electrolytic copper foil was placed on the adhesive sheet side of this adhesive-attached copper foil, and the resulting laminate was placed in a vacuum press and heated and pressed at 200 ° C for 90 minutes at 1 MPa (vacuum degree 5 torr) to form the laminate. The copper foil was then etched all over to obtain an adhesive film of about 20 μm, and the dielectric constant, dielectric loss tangent, and Tg were measured. The dielectric constant and dielectric loss tangent were measured by a cylindrical cavity resonator method in accordance with JIS C2565, and Tg was measured in accordance with IPC-TM-650-2.4.24.3. The storage stability was evaluated by transferring the adhesive composition into a sealed container and leaving it in a thermostatic chamber at 25° C., measuring the viscosity over time with a rheometer, and expressing it as the ratio of viscosity over time / initial viscosity.

[0079] The property evaluation results of the adhesive films produced from adhesive compositions 1 to 6 produced in Synthesis Examples 1 to 5 and adhesive compositions 7 to 9 produced in Synthesis Comparative Examples 1 to 3 are shown in the following Table 1. In Table 1, "-" for storage stability means not measured.

[0080] (Evaluation of various FCCL characteristics) Adhesive compositions 1 to 6 and adhesive compositions 7 to 9 were applied to a 25 μm polyimide film (KAPTON (registered trademark) (manufactured by Toray DuPont) 100EN, FS-100 (manufactured by SKC Corporation)) using a die coater and dried at a temperature of 160°C to produce a double-sided coated adhesive sheet in state B (film thickness on one side: 12 μm). The volatile content was adjusted to 0.6 wt%. Copper foil with a diameter of 12 μm and Rz = 1.8 μm was laminated on both sides of this adhesive sheet at 190°C, and then heat-treated in a dryer at 200°C for 90 minutes to produce a double-sided copper foil FCCL. Adhesive composition 8 had a large resin flow and the film thickness could not be controlled, so that a normal FCCL could not be produced by copper foil lamination and heat treatment.

[0081] The peel strength and solder heat resistance of the double-sided copper foil FCCL prepared as described above were evaluated. The results are shown in Tables 2-1 and 2-2 below. The test method was in accordance with JIS C 6471 and JIS C 6481. In addition, the dielectric properties (dielectric constant and dielectric loss tangent) of the double-sided copper foil FCCL were measured by a cylindrical cavity resonator method using a film in which the copper foil was entirely etched. As Comparative Example 5, the characteristics of a commercially available two-layer FCCL produced by a laminate method were evaluated.

[0082] [Table 1]

[0083] [Table 2-1]

[0084] [Table 2-2]

[0085] The results in Table 1 show that the films produced from adhesive compositions 1 to 6 of the present invention have a low adhesive composition dielectric constant and dielectric tangent, achieve a Tg of 110°C or higher, have very good storage stability, have a low water absorption rate, and have excellent solder heat resistance after moisture absorption, resulting in a well-balanced set of properties. Furthermore, from the results of Tables 2-1 and 2-2, it can be seen that the FCCLs using adhesive compositions 1 to 5 of the present invention (Examples 1 to 5) have an excellent balance of dielectric properties, solder heat resistance, and peel strength compared to the FCCLs using adhesive compositions 6 to 9 (Comparative Examples 1 to 3) and the two-layer FCCL by the laminate method. [Industrial Applicability]

[0086] By using the adhesive and adhesive sheet of the present invention, it is possible to provide a low dielectric two-layer FCCL by a laminate method that achieves a good balance between dielectric properties, thermal properties, processing properties, adhesive properties, moisture absorption properties, and cost.

Claims

1. The adhesive for flexible copper-clad laminates is used to bond a polyimide film substrate and copper foil that constitute a flexible copper-clad laminate, the adhesive comprising a solvent-soluble polyimide that has been subjected to dehydration ring-closure imidization and has a repeating unit represented by the following general formula [I], and a silane coupling agent represented by the following general formula [II] (excluding silane coupling agents having an amino group), wherein the dimer diamine residues contained in the solvent-soluble polyimide account for 20 mol % or more and less than 30 mol % of all diamine residues. 【Chemistry 1】 (In formula [I], Z is a bisphenol dianhydride residue, and Ar is a dimer diamine residue.) (2) 3 [II] (In formula [II], X is a group having a ketimine structure or an aldimine structure, and R is an alkyl group.)

2. 2. The adhesive according to claim 1, wherein the adhesive is heat-treated at 200°C for 90 minutes to give a film having a Tg of 110°C or higher.

3. 3. The adhesive according to claim 1, wherein the bisphenol dianhydride residues contained in the solvent-soluble polyimide account for 70 mol % or more of all dianhydride residues.

4. The adhesive according to any one of claims 1 to 3, wherein the adhesive contains a water-insoluble solvent, and the water-insoluble solvent is methyl benzoate.

5. The adhesive according to any one of claims 1 to 4, wherein a film obtained by heat-treating the adhesive at 200°C for 90 minutes has a dielectric tangent of 0.03 (5 GHz) or less and a dielectric constant of 3.0 (5 GHz) or less.

6. An adhesive sheet for flexible copper-clad laminates, comprising an adhesive layer for adhering copper foil laminated on one or both sides of a polyimide film substrate constituting the flexible copper-clad laminate, the adhesive layer containing the adhesive according to any one of claims 1 to 5.

7. A flexible copper-clad laminate comprising an adhesive layer and a copper foil laminated in that order on one or both sides of a polyimide film substrate, the adhesive layer containing the adhesive according to any one of claims 1 to 5.

8. A method for producing a flexible copper-clad laminate as described in claim 7, comprising laminating a copper foil to the adhesive sheet as described in claim 6 at a temperature of 220°C or less, and then heat-treating the adhesive layer at a temperature of 220°C or less.

Citation Information

Patent Citations

  • Flexible metallic foil polyimide laminated sheet and its manufacturing method

    JP2006007632A

  • Polyimide-based adhesive composition, cured product, adhesive sheet, laminate, and flexible printed board

    JP2013199645A

  • Copper clad laminate and printed wiring board

    JP2017121807A

  • Copper clad laminate sheet for flexible printed wiring board and flexible printed wiring board

    JP2018041961A

  • Modified polyimide, adhesive composition, copper foil with resin, copper-clad laminate, printed wiring board and multilayer substrate

    JP2018044136A